Al-â€˜AlÄqah baina UshÅ«l al-Fiqh wa MaqÄshidi al-SharÄ«ah wa al-Daâ€™wah ilÄ Taâ€™sÄ«si â€˜Ilmi al-MaqÄshid - Binti Ramli, Anggraini (Mazahib, 2016)
The study of MaqÄshid sharÄ«a is an important point in the discussion of Islamic legal theory (ushÅ«l al-fiqh). Serious debates began to emerge in the 19th century among Islamic jurists concerning the position of maqÄshid sharÄ«a. At least, there are three important debates in the history; first, whether maqÄshid is part of the discussion ushÅ«l al-fiqh; second, is maqÄshid sharÄ«a built upon a foundation of classical Islamic jurisprudence (fiqh); and third, whether the maqÄshid sharÄ«a study is able to become an independent science that is separated from the study of classical Islamic jurisprudence. This article tries to present a discussion of the three paradigms by employing a descriptive-analytic method. The results of this study uncover that the study of maqÄshid sharÄ«a is like two sides of one coin; theoretically it is a distinctive study from ushÅ«l al-fiqh, but it cannot be separated from one another.Â UshÅ«l al-fiqh has become the foundation to find out more details about the study of maqashid sharia.Â The separation between classical Islamic jurisprudence (fiqh)Â and maqÄshid sharÄ«a study conducted by Islamic jurists is a relative separation. Keywords: UshÅ«l al-fiqh, maqÄshid sharÄ«a, separation betweenÂ UshÅ«l al-fiqh and study of maqÄshid sharÄ«a.